1999
DOI: 10.1203/00006450-199909000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in Dilating the Fetal Ductus Arteriosus in Rats

Abstract: Prostaglandin E is a major dilator of the fetal ductus arteriosus (DA), but the role of nitric oxide in fetal ductal dilation has not been established. We studied the effects of a potent nitric oxide synthase inhibitor, Nomega-nitro-L-arginine methyl ester (L-NAME), on the fetal DA in rats. L-NAME was injected into the dorsum of pregnant rats, and fetal DA was studied 4 h later with a rapid whole body freezing method. The inner diameters of the DA and the main pulmonary artery were measured on a freezing micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 18 publications
5
64
1
1
Order By: Relevance
“…PGs have a major role in dilating the DA in near-term rats, whereas NO has a minor role; the reverse is true in premature DAs, in which the NO pathway predominates. 38 Accordingly, we show that PGH synthase and NO synthase inhibition enhanced O 2 constriction more in preterm than in term DAs. Nonetheless, O 2 constriction in the preterm DAs remained weaker, despite inhibition of PGH synthase and NO synthase (Figure 1).…”
Section: Discussionmentioning
confidence: 89%
“…PGs have a major role in dilating the DA in near-term rats, whereas NO has a minor role; the reverse is true in premature DAs, in which the NO pathway predominates. 38 Accordingly, we show that PGH synthase and NO synthase inhibition enhanced O 2 constriction more in preterm than in term DAs. Nonetheless, O 2 constriction in the preterm DAs remained weaker, despite inhibition of PGH synthase and NO synthase (Figure 1).…”
Section: Discussionmentioning
confidence: 89%
“…47 This report supports the study by Momma and Toyomo. 46 These findings including the present study suggest that NO inhibitors could be a therapeutic agent to prevent infection-related PDA, especially in immature fetuses. In addition to NO, it has been known that reactive oxygen species 48 and calpain 49 are therapeutic targets for inflammation-related vascular diseases.…”
mentioning
confidence: 80%
“…It should be noted that the dilatory effect of NO on the DA is more significant in immature fetuses. 45- 47 Momma and Toyono reported that NO, but not PGE2, played a major role in dilating the DA in preterm fetal rats (embryonic day 19), 46 and that the importance of NO was relatively decreased during development. 46 Clyman reviewed that the DA in preterm newborn produced an increased amount of NO after birth although the DA responded to PGE2 persistently.…”
mentioning
confidence: 99%
“…PGE 2 plays a major role in prenatal patency and postnatal closure of the mammalian DA, namely during fetal life by exerting a potent relaxant eVect (Clyman 2006;Smith 1998), possibly in conjunction with nitric oxide (NO, Coceani et al 1994;Momma and Toyono 1999;Seidner et al 2001;Takizawa et al 2000), and after birth by abruptly withdrawing its action. We have previously shown that the transition to ex ovo life is accompanied by dramatic changes in chicken DA reactivity (Agren et al 2007(Agren et al , 2008.…”
Section: Discussionmentioning
confidence: 99%